Analysis of the Effect of Natural Resources on the Quality of Human Development through Jambi Province Capital Expenditures - Fauzan Ramli; Yuliana Safitri (Sustainability (STPP) Theory, Practice and Policy, 2022)
The natural resources owned by each Regency/City in Jambi Province are different, this has an impact on regional progress, especially the level of human development. The important role of local governments in improving human development through spending in the field of education and health in particular. This study aims to analyze; (1) How natural resource revenue-sharing funds contribute maximally to Regency/City capital expenditures in Jambi Province (2) The effect of general mining revenue-sharing and oil-gas revenue-sharing funds on capital expenditures in Jambi Province, (3) Effect of mining revenue-sharing funds general and oil and gas revenue-sharing funds to the Human Development Index through capital expenditures in Jambi Province. This study uses quantitative descriptive analysis methods and path analysis,(2) The results of the multiple linear regression equation are general mining revenue sharing (X1) and shared funds. The results of oil and gas (X2) on capital expenditure show that the independent variable has a simultaneous effect with an R-Squared value of 0.7521 or 75.21% while the remaining 24.79% is influenced by other variables, (3) General mining revenue sharing directly had a significant effect on HDI was 2.92% and had an indirect effect of 0.29%, meanwhile the oil and gas profit sharing funds had no significant effect on HDI.